Radio emissions on improved forages for Kenya - Ohmstedt, Uwe (Bioversity International and the International Center for Tropical Agriculture, 2020)
Radio emissions are one way to transport messages and information to a wider public and are frequently used in countries where access to many people by individual contacts is cost intensive and slow. We had the intention to use this mean to reach out to the rural populations and especially to livestock keepers in Meru and Kisii.